Knowledge and Awareness about Anesthesia and Perception about Anesthesiologists and their Role during the COVID-19 Pandemic among Patients at a Zonal Hospital: A Cross-sectional Survey - Mayank Rajput; Dewendra J. Gajbhiye; Nagesh Venkata Ivaturi; Shambhavi Rajiva; Vivek Yadav (Journal of Marine Medical Society)
Background: Anesthesia forms the cornerstone of the practice of modern medicine as we know it today. The field of anesthesia has evolved beautifully since its conception in the 1800s and today the reach of the anesthesiologist goes far beyond his role in the OT. The most critical patients are managed by this fraternity, witnessed by the world during the tough times of the COVID-19 pandemic. However, even today, in the 21st century, anesthesia functions in relative obscurity, succinctly labelled as a ‘behind the screen’ specialty by the medical fraternity itself. Aims and Objectives: Conducted in the aftermath of the pandemic, the research was aimed to assess the general knowledge among patients regarding the branch of Anesthesia and understanding the public perception regarding Anesthesiologists, including their role inside and outside the OT, especially during the Covid-19 pandemic. In addition, the sources of patient information and significant association with age, gender, literacy level and employment status were explored by our study. Materials and Methods: A quantitative cross-sectional survey was conducted at a secondary-care government hospital and a total of 307 participants were enrolled in the study. After a detailed structured interview with participants, the data was tabulated in Excel form and statistical analysis was done for association with demographic variables. Results: The results, viewed against a background of previous similar national and international studies, revealed significant ignorance regarding this specialty and poor improvement as compared to previous data, despite having been in the limelight owing to the recent pandemic. Only 58% participants had heard the term ‘Anesthesia’ and 38% were aware of what it achieves in a patient. About three-fourths of them knew the anesthesiologist as a qualified doctor but only 50% considered his job equivalent to that of the surgeon. The main source of knowledge was by word of mouth followed by prior exposure to anesthesia. Furthermore, the study revealed that the level of the patient’s education controlled with the patient’s age and employment factors was the significant predictor of their knowledge, awareness and perception regarding anesthesia and role of anesthesiologists (p<0.05). The patients with secondary and above level education, the younger age groups and those who were currently employed were significantly better informed. Conclusion: The results of the research, compared with previous data of Indian and International studies since the last two decades, demonstrated a clear lack of improvement in public knowledge levels. This was unexpected considering how the recent pandemic brought the entire medical community into the limelight, some of which should have been shed on Anesthesiologists as well. Additionally, there is a stark difference between the populations of developed and developing countries seen in several post pandemic studies. The ignorance continues to pervade all aspects of the anesthesiologist’s job including his purview beyond the OT. A fresh perspective was obtained through the demographic factors brought out by the study, elucidating that the anesthesia fraternity needs to focus on improving communication with certain subsets of their patients (like the elderly, the unemployed and illiterate). Several conjoint endeavors are required between the government the professional community to increase the public cognizance and appreciation that all current and future anesthesiologists, deserve.